Miscibility as a Factor for Component Crystallization in Multisolute Frozen Solutions. Issue 7 (5th June 2014) - Izutsu, Ken‐Ichi; Shibata, Hiroko; Yoshida, Hiroyuki; Goda, Yukihiro
<x xml:space="preserve">Abstract</x> The relationship between the miscibility of formulation ingredients and their crystallization during the freezing segment of the lyophilization process was studied. The thermal properties of frozen solutions containing myo‐inositol and cosolutes were obtained by performing heating scans from −70°C before and after heat treatment at −20°C to −5°C. Addition of dextran 40, 000 reduced and prevented crystallization of myo‐inositol. In the first scan, some frozen solutions containing an inositol‐rich mixture with dextran showed single broad transitions (Tg′s: transition temperatures of maximally freeze‐concentrated solutes) that indicated incomplete mixing of the concentrated amorphous solutes. Heat treatment of these frozen solutions induced separation of the solutes into inositol‐dominant and solute mixture phases (Tg′ splitting) following crystallization of myo‐inositol (Tg′ shifting). The crystal growth involved myo‐inositol molecules in the solute mixture phase. The amorphous–amorphous phase separation and resulting loss of the heteromolecular interaction in the freeze‐concentrated inositol‐dominant phase should allow ordered assembly of the solute molecules required for nucleation. Some dextran‐rich and intermediate concentration ratio frozen solutions retained single Tg′s of the amorphous solute mixture, both before and after heat treatments. The relevance of solute miscibility on the crystallization of myo‐inositol was also indicated in the systems containing glucose or recombinant human albumin. © 2014 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 103:2139–2146, 2014